2011
DOI: 10.1002/jmv.22008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and association of human parvovirus B19V with hepatitis B and C viruses in Nigeria

Abstract: Background In the course of setting up the National Mesothelioma Surveillance Program (PNSM), established in France in 1998, the question arose as to the most suitable method of assessing occupational exposure. The aim of this study was to define the most suitable rating method for assessing occupational asbestos exposure in order to assess medico‐social care. Method The study included 100 subjects—50 cases of mesothelioma and 50 controls—randomly selected and representing 457 jobs held. Job asbestos exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
2
13
3
Order By: Relevance
“…The prevalence of 4% and 13.2% were observed among pregnant women in Oyo State [18] and Nasarawa State [19], respectively. Though this study showed a high prevalence of anti-B19V IgM among SCD patients, it was conversely lower than the findings of few other Nigerian studies, including Iwalokun et al [9] in which 17.8% was recorded; Opaleye et al [20] also recorded 32% among a non-hepatitis control group. These variations in the prevalence of anti-B19V IgM may not be unconnected with the characteristics of the populations studied, the sample sizes used in these studies, and the assay kits' sensitivities and specificities.…”
Section: Discussioncontrasting
confidence: 94%
“…The prevalence of 4% and 13.2% were observed among pregnant women in Oyo State [18] and Nasarawa State [19], respectively. Though this study showed a high prevalence of anti-B19V IgM among SCD patients, it was conversely lower than the findings of few other Nigerian studies, including Iwalokun et al [9] in which 17.8% was recorded; Opaleye et al [20] also recorded 32% among a non-hepatitis control group. These variations in the prevalence of anti-B19V IgM may not be unconnected with the characteristics of the populations studied, the sample sizes used in these studies, and the assay kits' sensitivities and specificities.…”
Section: Discussioncontrasting
confidence: 94%
“…B19 was also co-detected in the sera of HBV-infected patients. A significant correlation exists between HBV/B19 co-infection using serum samples from Vietnamese and Nigerian subjects [17], [18]. However, the data in our study did not support the conclusion that B19 infection increased the frequency of HBV co-infection.…”
Section: Discussioncontrasting
confidence: 93%
“…Co-infection of parvovirus B19 and PARV4 with HBV or hepatitis C (HCV) has been observed in patients with acute and chronic hepatitis [17], [18]. In the southern region of China, HBV infection is endemic, with an HBsAg seroprevalence of approximately 7–9% [21], [22]; however, the seroprevalence of HPAV among the HBV infection individuals in this area is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…B19V-genotype 1, and especially B19V-genotype 1A, was the most prevalent genotype in Gabonese children. This is in accordance with previous studies showing a predominance of B19V-genotype 1 worldwide [31,35,48,49]. Interestingly, B19V genotype 2 was found in 28.6% of the young Gabonese children.…”
Section: Discussionsupporting
confidence: 93%